Market Participants' Strategies In Monopoly And Oligopoly Systems: A Qualitative Perspective - Muhammad Daffa Fahrezy; Dafa Rizky Suhana; Nazwa Fadillah; Sanusi Ghazali Pane (Journal of Research in Social Science and Humanities, 2025)
This study examines the strategies employed by market players in monopoly and oligopoly systems and their impact on business competition dynamics. Using a qualitative approach, data were collected through interviews, observations, and document analysis. The findings reveal that in monopolies, market players leverage dominance to control prices and resources, whereas in oligopolies, collaborative and selective competition strategies are adopted to maintain market stability. These strategies significantly affect innovation challenges, market access inequality, and the need for effective regulatory policies. This research provides recommendations to enhance market balance and consumer protection through strengthened regulation and policy monitoring.